ANTIBIOTIC RESISTANCE TRENDS AND MICROBIOLOGICAL PROFILE OF URINARY TRACT INFECTIONS: A CROSS-SECTIONAL STUDY - Dr. Khutija Sarah; Dr. Murtaza Ahmed Khan; Dr. Ayesha Nazar; Dr. Shaheen Bhat (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Introduction: Urinary tract infection (UTI) is one of the most common bacterial infections, with changing trends in antimicrobial susceptibility due to widespread antibiotic use. This study was conducted to determine the prevalence of UTI and the current antibiotic susceptibility patterns of uropathogens. Materials and Methods: This was a retrospective analysis carried out in the Department of Microbiology and Department of General Medicine at a tertiary care centre. Patient demographics, organisms isolated, and antibiotic susceptibility profiles were recorded and analyzed. Results: The overall prevalence of UTI was 33.5% (419/1250), with 280 (66.8%) female and 139 (33.2%) male cases. The majority of cases were observed in middle-aged females (31–45 years) and elderly males (>45 years). The most common uropathogen was E. coli (225/419, 53.7%), followed by Klebsiella pneumoniae (115/419, 27.4%), Pseudomonas aeruginosa (36/419, 8.6%), Proteus spp. (20/419, 4.8%), Enterobacter spp. (7/419, 1.7%), and Staphylococcus aureus (6/419, 1.4%). Meropenem, gentamicin, nitrofurantoin, and cotrimoxazole were the most effective antibiotics, while high resistance was noted against amoxicillin, fluoroquinolones, and third-generation cephalosporins. Conclusion: Regular surveillance of antimicrobial susceptibility is essential to guide empirical therapy in UTI and to prevent the emergence of resistant strains.